The Fashion Being between body and technology: a phenomenology of portable (ModaPalavra e-periódico, 2021)
This paper presents the concept of Fashion Being as the whole relationship of a body dressed or adorned, without clothes or in clothes without bodies. The development of technology is presented as an essential human relationship: man as an inseparable entity of technique, the maker of his body artifacts, which define him as a producer and user of his tools and ornaments. Examples of wearable technology are provided from discovered archaeological forms to contemporary mechanisms linking industrial revolution, arts, fashion and medicine. The intrinsic use of equipment, from the primitive bags for hunting and transporting objects to modern smartphones, provoke a reflection on reality and phenomenology of portable contemporary.
Keywords: fashion; technology; phenomenology of portable